2017
DOI: 10.1148/radiol.2017161055
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations in Chronic Capsular versus Pontine Stroke

Abstract: Purpose To investigate whether patients with capsular stroke (CS) and patients with pontine stroke (PS) involving the motor pathway have different types of structural damage and reorganization. Materials and Methods With institutional review board approval and after obtaining written informed consent, structural magnetic resonance imaging data were prospectively acquired in 115 patients with CS, 47 patients with PS, and 116 control subjects by using four imagers from three hospitals. Patients with stroke lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
11
28
1
Order By: Relevance
“…They are the most common sites of IS that involve the subcortical motor pathway. It is well-known that focal IS leads to extensive structural and functional remodeling (10, 11). However, it remains unclear whether pontine stroke (PS) and corona radiata stroke (CRS) differ in the patterns of the functional remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…They are the most common sites of IS that involve the subcortical motor pathway. It is well-known that focal IS leads to extensive structural and functional remodeling (10, 11). However, it remains unclear whether pontine stroke (PS) and corona radiata stroke (CRS) differ in the patterns of the functional remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unknown whether the rubral branches are differentially involved in the stroke, which is important for understanding the roles of each rubral branch in stroke-induced disability and recovery. Early studies have also shown that the lesion locations of stroke were closely associated with the types and severity of dysfunction and recovery potentials (Cheng et al., 2014); moreover, different infarction location can induce differential types of structural damage and reorganization of brain gray matter, even in brain regions outside of the lesion (Jiang et al., 2017). Thus, it also interesting to elucidate whether the patterns of damage/reorganization of the rubral branches are also lesion-location dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other subcortical lesions normally reported in previous studies (mostly located in the internal capsule and neighboring regions), the pontine region is a subtentorial structure remote from the cerebral cortex. A recent study has demonstrated different patterns of whole-brain structural damage in patients with pontine stroke and capsular stroke ( 19 ). Therefore, we suppose patients with pontine infarction would present different patterns of functional impairment compared with other infarcts.…”
Section: Introductionmentioning
confidence: 99%